A unique case of cutaneous melanoma: case report and literature review - Iulia Maria Teodora Leulescu; Grigore Bălan; Claudia Ioana Dogaru; Maria Moga; Emil Cătălin Popa; Irina Popescu; Mircea Tampa; Simona Roxana Georgescu (Journal of Mind and Medical Sciences)
Introduction. According to the European Cancer Information System, melanoma is the sixth most diagnosed cancer in Europe (following breast, colorectal, prostate, lung, and bladder cancer) and ranks among the top 20 most common causes of cancer-related death. The diagnosis of melanoma can be a clinical challenge due to the variety of signs and symptoms, ranging from small, asymptomatic lesions with slow progression to large, painful tumors with rapid growth. In this paper, we will report an exceptional case of cutaneous melanoma with an atypical presentation in a patient with no personal or family history of skin cancer. Case presentation. We present the case of an 85-year-old patient who presented to our dermatology clinic with multiple nodular lesions on her right calf, extending to her thigh as isolated lesions. These violaceous lesions varied in size and displayed signs of bleeding, fibrin deposits, and purulent, foul-smelling discharge. The patient reported a fivemonth history of rapid tumor progression. The initial presumptive diagnosis was Kaposi's sarcoma; however, the biopsy ruled out this diagnosis, revealing the presence of malignant melanoma. Given the extensive locoregional spread and invasion of deep structures, the patient was transferred to palliative care. Conclusions. Melanoma is an aggressive form of cancer that can rapidly progress, often presenting with atypical clinical manifestations or mimicking other skin conditions. When the clinical presentation deviates from the classic patterns, a biopsy is considered the gold standard for guiding the clinician's subsequent approach. It provides valuable diagnostic information and aids in determining the prognosis as well as the appropriate therapeutic course.